Application of priming agents in red raspberries prior to transplantation and at pre-flowering stages results in improved yield efficiency and enhanced secondary metabolism - Valanides, Nicolas; Georgiadou, Egli C.; Myrtsi, Eleni D.; Gil, Carlos Javier Garcia Hernandez; Taliadorou, Anna-Maria; Torrado, Sofia O.C.A.; Hertog, Maarten L.A.T.M.; Tomás-Barberán, Francisco A.; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2025)
Red raspberry (Rubus idaeus L) fruit has high nutritional value and there is an increasing demand in its global cultivation, highlighting the need for sustainable practices to improve both fruit and plant productivity. Chemical priming has recently gained attention as a sustainable horticultural crop management approach to enhance plant performance. In the current study, the effects of multiple chemical priming agents were investigated on their potential to improve yield efficiency, enhance antioxidant potential and fruit quality attributes, with special reference to aroma of ‘Vica Abril’ raspberry plants. Treatments included: (1) NOSH-aspirin (NOSH-A, 100 μM), (2) melatonin (Mel, 100 μM), (3) sodium alginate (NaA, 0.5 % w/v), (4) sodium alginate-melatonin conjugate (NaA/Melatonin, 100 μM/0.5 % w/v), and (5) glycine-betaine (GB, 10 mM). Additionally, control treatments included application of water (hydro-primed) and DMSO (0.1 % v/v) (solvent control for NOSH-A). Treatment application was initially performed pre-planting at the root zone and subsequently at 27, 46 and 74 days after planting (DAP). Melatonin treatment significantly enhanced fruit yield, particularly during the early harvests, while NOSH-A enhanced sucrose and ascorbic acid content and all priming agents increased total flavonoid content. Treatments with NaA alone or in conjugated form with Mel led to a considerable increment of kaempferol, several anthocyanins and ellagic acid derivatives, among the 13 polyphenolic compounds identified. The analysis of volatile organic compounds (VOCs) in raspberry fruits identified a total of 98 distinct compounds. Besides d-limonene content, no striking differences in aroma composition was monitored among treatments tested. The application of priming agents, most promptly melatonin, is a promising technological approach that needs to be further exploited towards increased crop productivity and/or enhanced raspberry fruit quality.
Keywords: Primary metabolism; Primocane; Production models; Rubus idaeus; Secondary metabolism; Sustainability